Multiuser demodulation and iterative decoding for frequency-hopped networks. - Sharma, N.
Demodulation and decoding for frequency-hopped spread-spectrum multiple-access (FH/SSMA) systems have been traditionally conducted by conventional single-user (noncollaborative) demodulation and error- and erasure-correcting decoding techniques. In this paper, we study the demodulation and decoding aspects of collaborative multiuser reception for FH/SSMA and propose methods which increase the number of users the system can support. In particular, we propose and analyze the optimum maximum a priori probability demodulation of multiple symbols or type, and the use of iterative multiuser decoding after the demodulation. Since hits from one or two other users are the most likely hit events in FH/SSMA, the joint demodulation of two or of three users is performed based on likelihood ratio tests. M-ary frequency-shift keying modulation with noncoherent demodulation and Reed-Solomon codes with hard-decision minimum distance decoding are used in the FH/SSMA system. Results are derived for both synchronous and asynchronous frequency-hop systems. The performance of the proposed multiuser detector in additive white Gaussian noise and flat Rayleigh fading channels is evaluated. Scenarios when all simultaneous users or only a subset of them are collaboratively demodulated and decoded are simulated
Keywords: FH/SSMA.; M-ary frequency-shift keying modulation; Reed-Solomon codes; Additive white Gaussian noise channels; Asynchronous frequency-hop systems; Collaborative multiuser reception; Flat Rayleigh fading channels; Frequency-hopped networks; Frequency-hopped spread-spectrum multiple-access systems; Hard-decision minimum distance decoding; Iterative decoding; Likelihood ratio tests; Maximum a priori probability demodulation; Multiple symbols; Multiuser demodulation; Noncoherent demodulation; Synchronous frequency-hop systems